مدى توافر متطلبات الإفصاح لبازل III في المصارف العراقية: دراسة حالة في المصرف الأهلي العراقي - الجعفري، سندس ماجد رضا; السعبري، منتظر رسول عبد Alsaabari, Muntazar Rasoul Abd (جامعة بابل - كلية الإدارة والاقتصاد, 2019)
هدفت الدراسة إلى بيان إمكانية تطبيق متطلبات الإفصاح لبازل 3 في المصارف العراقية. إذ سعت لجنة بازل إلى تحقيق الاستقرار المالي في الأسواق العالمية وتحقيق الشفافية ومساعدة مستخدمي التقارير المالية في تقييم كفاية راس المال والمخاطر التي تواجه القطاع المصرفي فضلا عن تسهيل عملية المقارنة بين المصارف النشطة دوليا وذلك من خلال ركيزتها الثالثة (انضباط السوق) والتي تعد مكملة للركيزتين السابقتين (كفاية راس المال والرقابة الإشرافية) ولتحقيق هذه الأهداف فقد وضعت اللجنة قوالب ثابتة للإفصاح. ومن أهم النتائج التي توصلت إليها الدراسة هي أن المصارف العراقية لاتزال في بداية تطبيقها للركيزة الأولى من اتفاقية بازل 3 وأنها بدأت بتحسين مستوى الإفصاح وإتاحة المعلومات للمستخدمين من خلال مواقعها الإليكترونية وبشكل متكرر خلال السنة مما يعني إمكانية تبني متطلبات الإفصاح لبازل 3 وتطبيقها على أرض الواقع. The study aimed to clarify the possibility of applying the disclosure requirements of Basel 3 in the Iraqi banks. The Basel Committee sought to achieve financial stability in the global markets and to achieve transparency and to assist users of financial reports in assessing the adequacy of capital and risks facing the banking sector as well as facilitating the process of comparison between internationally active banks through its third pillar (market discipline), which is complementary to the two concentrations (Capital Adequacy and Supervisory Control). To achieve these objectives, the Committee has established fixed templates for disclosure. One of the most important findings of the study is that Iraqi banks are still at the beginning of their implementation of the first pillar of Basel III and it began to improve the level of disclosure and provide information to users through their websites and frequently during the year, which means the possibility of adopting the requirements of disclosure to Basel 3 and applied on the ground.
Keywords: المصارف -- العمل المصرفي -- الإفصاح المحاسبي -- القوائم المالية -- بازل 3 -- المصرف الأهلي العراقي